(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: this study aims to This study aimed to examine selected cognitive characteristics in older adults with mild cognitive impairment (MCI). Subjects and Methods: the study was conducted on 40 elderly patients diagnosed with MCI at the National Geriatric Hospital from July 2024 to April 2025. Evaluated parameters included: MMSE, verbal memory, visual memory, attention, language, visuaconstruction, executive dysfunction Results: Delayed memory was the most impaired domain: 85% performed below normal on delayed word and figure recall, and 57.5% on delayed story recall. Immediate recall showed mild-to-moderate impairment, while recognition remained relatively preserved. Naming, simple attention, and basic executive tasks were largely intact. Strong correlations were observed among delayed memory tests (r = 0.53–0.75), whereas immediate and delayed recall correlated only moderately. Recognition measures correlated highly (r = 0.77). Conclusion: Comprehensive memory assessment is valuable for distinguishing MCI from normal aging and identifying individuals at risk of progression to Alzheimer’s disease.